EFEKTIVITAS PELAKSANAAN PENANGANAN PENYAKIT HIPERTENSI PADA PASIEN DOKTER KELUARGA DI KECAMATAN TURI, KABUPATEN SLEMAN PERIODE TAHUN 2011-2013 - , MUTHIA MUKHAROMA ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Background Hypertension now has become non communicable disease with the biggest prevalence in community and the leading risk factor for any cardiovascular diseases. Management of hypertension needs many approaches like holistic, comprehensive, and continuity of care which become the responsibility of the health provider. Therefore, family physician as the first gate of primary care should beable to perform an effective management of hypertension. Beside, right now the report for effectiveness of hypertension management in primary care is still very limited in Indonesia. Objective The aim of this study is to know the effectiveness of hypertension management by family physician in Turi District, Sleman from 2011 until June 2013. MethodThe data from medical records and hypertension monitoring book of 215 patients in a private family physician clinic from January 2011 until June 2013 were taken and analyzed. There was also a survey conducted to explore the patientsâ lifestyle and education received by them from their physician. ResultThe trend of blood pressure is decrease from 2011 to 2013. In the beginning of 2011, the mean BP 170/90 mmHg and then decreased by June 2013 to 144/84 mmHg. The goal of therapy achieved increased from 10,1% in 2011 to 43,6% in 2013. On June 2013, the majority of patients have BP in range of 140-159/90-99 mmHg. Variation of the drugs used for medication dominated by Amlodipine from class Calcium Channel Blocker. Physician tends to use monotherapy compared to combination therapy for hypertension. The referral rate was decreased by 15,5% to 5,21% on June 2013. Physician has given education for lifestyle in about 50% of the patient but the application by the patient is still very low. Conclusion The management of hypertension by family physician is considered good enough because there was a decrease of BP trends, an increase of goal therapy achievement, and the low referral rate. But physician should give more education to the patient about lifestyle since many of them still have bad lifestyle.